1990
DOI: 10.1128/jb.172.3.1289-1296.1990
|View full text |Cite
|
Sign up to set email alerts
|

Genes for phycocyanin subunits in Synechocystis sp. strain PCC 6701 and assembly mutant UV16

Abstract: The cyanobacterial phycobilisome is a large protein complex located on the photosynthetic membrane. It harvests light energy and transfers it to chlorophyll for use in photosynthesis. Phycobilisome assembly mutants in the unicellular cyanobacterium Synechocystis sp. strain 6701 have been characterized. One such mutant, UV16, contains a defect in the assembly of the biliprotein phycocyanin. We report the cloning and sequencing of the phycocyanin genes from wild-type Synechocystis strain 6701 and demonstrate an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

1990
1990
1995
1995

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 45 publications
1
22
0
Order By: Relevance
“…This observation suggests that posttranscriptional processes may be important in establishing PE levels in Analysis of PE genes in a phycoerythrin assembly mutant. One approach to studying phycobilisome structure and assembly has involved the analysis of UV-induced phycobilisome assembly mutants in Synechocystis strain 6701 (2)(3)(4). The UV16 mutant is defective in PC assembly, but it also exhibits other aberrant characteristics such as decreased levels of PE (55% that of the WT) and an abnormal response to red light during chromatic adaptation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This observation suggests that posttranscriptional processes may be important in establishing PE levels in Analysis of PE genes in a phycoerythrin assembly mutant. One approach to studying phycobilisome structure and assembly has involved the analysis of UV-induced phycobilisome assembly mutants in Synechocystis strain 6701 (2)(3)(4). The UV16 mutant is defective in PC assembly, but it also exhibits other aberrant characteristics such as decreased levels of PE (55% that of the WT) and an abnormal response to red light during chromatic adaptation.…”
Section: Resultsmentioning
confidence: 99%
“…Mutagenesis of UV16 resulted in the UV16-40 that is defective in both PC and PE assembly (4). Cyanobacteria were grown as previously described (2). The Escherichia coli strains used in this study were JM101, for M13 cloning and the isolation of sequencing templates (31) (26), and the Sau3AI ends were partially filled in with A and G residues by using the Klenow fragment of DNA polymerase I.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…a-C-PE a-C-PE a-B-PE a-B-PE a-C-PE a-B-PE a-PE-I1 a-PE a-PEC a-PEC a-R-PC-I a-R-PC-I1 a-C-PC-I a-C-PC-I1 a-C-PC-111 a-C-PC a-C-PC Anderson andGrossman (1990) Fiiglistaller et al (1983), Eberlein and Kufer (1990) Swanson et al (1992) this work, submitted to data banks (1994) De Lorimier et al (1993, Conley et al (1988) Capuano et al (1988), Conley et al (1988, Mazel and Marliere (1989) Belknap andHaselkorn (1987) Offner et al (1981) Frank et al (1978), Kufer, W., Hoenger, A., Eberlein, M., Mayer, K.,…”
Section: Supplementmentioning
confidence: 99%
“…, Pilot and Fox (1984) Walsh et al (1980) Lau et al (1987a), Kalla et al (1988) Wilson et al (1991) Anderson and Grossman (1990) Apt and Grossman (1993b) Minami et al (1985) Offner and Pilot and Fox (1984), Glazer (1987) Freidenreich et al (1978), Williams and Glazer (1978), Glazer (1987) Lau et al (1987b), Kalla et al (1988) Wilson et al (1991 Anderson and Grossman (1990) Sidler et al (1990) Apt and Grossman (1993b) Minami et al (1985) Offner and Troxler (1983) Bryant et al (1985) Sidler et al (1981, Riimbeli et al (1987) Houmard et al (1986, Klotz et al (1986) Su et al (1992 Some cyanobacteria are found under several names depending on the publications and the data banks. For clarity, only the most common used strain designations (from the point of view of the authors) have been used for the table above.…”
mentioning
confidence: 99%